2022
DOI: 10.1080/14999013.2021.1947422
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Inhibition and Activation System Factors in Offenders and Non-Offenders

Abstract: Objective: The main aim was to investigate whether forensic psychiatric inpatients can be distinguished from prisoners and non-offender healthy controls based on their performance on neurocognitive tasks measuring behavioral inhibition and behavioral activation. Method: This study used preexisting data from 120 male forensic psychiatric inpatients, 60 male prisoners and 66 male non-offender healthy controls. A multinomial logistic regression analysis was used to study the links between our outcome measures and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 93 publications
1
4
0
Order By: Relevance
“…Weaknesses in these cognitive domains have robust positive associations with aggressive and criminal behavior (Morgan & Lilienfeld, 2000; Ogilvie et al, 2011; Portnoy et al, 2013; Janes et al, 2024; Jansen & Franse, 2024). Similar results have been obtained in forensic (psychiatric) inpatient populations as well (Molleman, Driessen, et al, 2022; Molleman, Molleman, et al, 2022; Shumlich et al, 2019). However, recent research did not demonstrate any decrements in memory, orientation, language, and visuospatial skills within the prison and outpatient forensic (psychiatric) population (Fassaert et al, 2022).…”
supporting
confidence: 86%
See 3 more Smart Citations
“…Weaknesses in these cognitive domains have robust positive associations with aggressive and criminal behavior (Morgan & Lilienfeld, 2000; Ogilvie et al, 2011; Portnoy et al, 2013; Janes et al, 2024; Jansen & Franse, 2024). Similar results have been obtained in forensic (psychiatric) inpatient populations as well (Molleman, Driessen, et al, 2022; Molleman, Molleman, et al, 2022; Shumlich et al, 2019). However, recent research did not demonstrate any decrements in memory, orientation, language, and visuospatial skills within the prison and outpatient forensic (psychiatric) population (Fassaert et al, 2022).…”
supporting
confidence: 86%
“…Recent studies that examined similar forensic psychiatric populations compared to healthy controls (Molleman, Driessen, et al, 2022;Shumlich et al, 2019), also found no differences in performance between the groups on items of abstract reasoning. Even though abstract reasoning is believed to be strongly associated with EF (e.g., Wachholz & Yassuda, 2011), there is no consensus in the literature.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Indeed, excessive BAS activation has frequently been linked to impulsivity (i.e., Wallace et al, 2009) and aggression (Wingrove & Bond, 1998). Moreover, a recent study (Molleman et al, 2021) showed that the BIS/BAS self-report questionnaire seemed to dissociate between forensic psychiatric inpatients and prisoners. One next step would be to examine if the BIS/BAS also captured part of the group differences in the likelihood of recidivism or treatment responsivity (Molleman et al, 2021).…”
Section: Discussionmentioning
confidence: 99%